Lais Myrrha: the architecture of the world as a matter of art (Palíndromo, 2022)
This article proposes to analyze two works by the Brazilian artist Lais Myrrha, Borders Theory (2007) and Double Standard (2016), in order to unveil aspects of her poetic construction. The artifacts, which deal with the deconstruction of the real and symbolic boundaries that organize our existence, with the advance of modern technique and the threat of collapse that its instrumentalized use implies, give clues to your interest in, turning over the ruins that accumulate in the present, reflect, through the categories of time and space, how the things of the world are architected. By articulating the images from other narratives, by changing the references of what is seen and the meanings that are ordinarily attributed to her, the artist messes up the order of things, upsets the hierarchies and brings out the power of the destruction of everything that it seems necessary and inevitable.
Keywords: Lais Myrrha; Contemporary Art; Ruins; Destruction; Impermanence